LncRNA APTR Promotes Uterine Leiomyoma Cell Proliferation by Targeting ERα to Activate the Wnt/β-Catenin Pathway - Zhou, Weiqiang; Wang, Guocheng; Li, Bilan; Qu, Junjie; Zhang, Yongli (Frontiers in Oncology, 2021)
The molecular mechanisms by which uterine leiomyoma (UL) cells proliferate are unclear. Long noncoding RNA (lncRNA) is reported to participate in the occurrence and development of gynecological cancers. We investigated the molecular mechanisms that lncRNA uses in UL. We found that lncRNA Alu-mediated p21 transcriptional regulator (APTR) showed higher expression in UL tumor tissues compared with that in normal uterine tissues. APTR induced cell proliferation and colony formation both in vitro and in vivo. The JASPAR database showed that APTR was likely interacted with ERα, and these molecules were identified via laser scanning confocal microscopy and RNA immunoprecipitation analysis. To verify the correlation between APTR and ERα, we overexpressed and underexpressed APTR and simultaneously expressed ERα. The results showed that APTR function was suppressed. APTR increased the expressions of the proteins in the Wnt pathway, and inhibiting ERα eliminated these responses. In conclusion, our data suggest that APTR promoted leiomyoma cell proliferation through the Wnt pathway by targeting ERα, suggesting a new role of APTR in the Wnt signaling pathway in UL.